The Role of Internet in Successful Marketing in Tourism Organizations - UKAJ, Fatos (Journal of Environmental Management and Tourism, 2019)
Tourism has been dealt with continuously since the earliest times. This was done without entering into the essence of the motive of satisfying the needs of individuals and groups then and now. Various tourist destinations need to be introduced to the wider public. Therefore, a range of information needs to be distributed to the public by agencies, tourism operators, and other participants in tourist activities. The use of the internet has become a daily routine guiding tourism organizations’ marketing, including hospitality and tourism oriented towards meeting the demands of tourists and clients in general. By analyzing the trends in terms of the use of the internet and factors affecting marketing in tourism and hospitality, this paper focuses on its role and importance in the tourism business. The use of internet technology in hotel marketing activities was also analyzed.